USAGE OF ZINC-SILICATE COATINGS IN FRICTION CONNECTIONS - Fric, Nenad; Buđevac, Dragan; Mišković, Zoran; Marković, Zlatko; Dobrić, Jelena; Spremić, Milan (Journal of Applied Engineering Science, 2016)
Usage of zinc-silicate coatings as anti-corrosive protection of friction connections results in reduction of construction time and provides protection from corrosion. Such protection system has a number of advantages in respect to the widely implemented metallization procedure, prevalently in terms of speed of implementation, required training of the workforce and cost. In this paper were presented friction coefficients for different systems of anti-corrosive protection of friction connections, with emphasis on the zinc-silicate coatings and their technical characteristics and implementation methods.